Fundación Mazda, para el arte y la ciencia, décima segunda entrega de becas (2003)
In the beginning of sciences, such as mathematics and physics, all long to the academic history, from the ancient greeks to the modem mathematicians, there was a great deal ofscientifical insolved questions or solved much later with different scientifical tools, Right now, in the beginning ofthe third Millennium, scientist ask for solution to complet modern problems ofphysics.